Inorganic pollutants in used windows - Boštjan Lesar; Miha Humar (Les, 2020)
Although the circular economy and use of secondary raw materials are becoming increasingly important, recycled wood is currently still very poorly utilised, with most used to produce energy. One potential sources of recycled wood is old wooden windows. Many wooden windows are now being replaced due to inadequate energy characteristics, while such wood is often still in good condition, without signs of decay. The main problem with the use of wood from used windows for the production of new products is surface coatings. The study examined the influence of age, type and surface treatment on the proportion of inorganic pollutants. First, all non-wood materials were removed from the window profiles. Afterwards, the profiles were cut into the 5 mm thick slides, to measure how deeply the inorganic contaminants penetrated into the wood. The wood was analysed with an X-ray fluorescent spectrometer, and the concentrations of individual inorganic pollutants were determined (Cr, Cu, Cl, Fe, Zn, Pb). The results showed that the concentrations of inorganic pollutants depended on the age of the windows and the surface protection used. This study has shown that used windows can be a raw material for the production of new products and materials, provided that the surface layer is removed before use.